Pendekatan Hermeneutika Negosiatif-Otoritatif Speaking in God's Name: Islamic Law, Authority, and Women Pemikiran Khaled M Abou El Fadl - Ahmad Nuruddin (Discovery, 2024)
This study discusses how Khaled Abou El Fadl thinks in interpreting religious texts, namely the Qur'an and Hadith. In this case, it is done to be able to understand a religious text which is done by means of negotiation between the text, the writer, and the reader. This research uses a qualitative descriptive method, with library research as the type of this research. The data and data sources were taken from books, journals, and the works of Khaled Abou El Fadl. The documentation method is used as a data collection method, while for data analysis using content analysis. In.this.study, it can.be.seen.the results of Khaled Abou El.Fadl's hermeneutical interpretation of a religious text, namely the Qur'an and Hadith. This can determine the form of interpretation by negotiating between the text (text), author (author), and reader (reader) with a triadic pattern, namely an equilateral triangle, so that all posts have the same portion. Khaled's thought in the interpretation of this text is a renewal to be able to understand the text of the Qur'an and Hadith as the object of this interpretation.